OPTIMALISASI KEPATUHAN WAJIB PAJAK DALAM SISTEM PERPAJAKAN MODERN DI KANTOR PELAYANAN PAJAK PRATAMA MAKASSAR SELATAN - Djafar Djafar; Intan Ansar; Indah Indah; Erni Virda Apriliani; Agustina Adinda Putri; Deska Maharani; Putri Sofyan (Universitas Ichsan Sidenreng Rappang, 2026)
This study aims to determine and analyze the effect of the implementation of the modern tax system on taxpayer compliance. The modern tax system is a form of tax administration reform implemented by the government through the Directorate General of Taxes (DGT) by utilizing information technology, simplifying administrative procedures, and improving the quality of services provided to taxpayers. This study employed a quantitative approach to examine the effect of the modern tax system as the independent variable on taxpayer compliance as the dependent variable. Data were collected by distributing questionnaires to 100 registered taxpayers at the South Makassar Primary Tax Office (Kantor Pelayanan Pajak Pratama Makassar Selatan) as the research respondents. Furthermore, the collected data were analyzed using simple linear regression to determine the magnitude of the effect of the modern tax system on taxpayer compliance. The results indicate that the implementation of the modern tax system has a positive and significant effect on taxpayer compliance at the South Makassar Primary Tax Office. Based on the t-test results, the calculated t value was 3.726, while the t table value was 1.984, indicating that the calculated t value was greater than the t table value (3.726 > 1.984). In addition, the significance value was less than 0.05, indicating that the research hypothesis was accepted. Therefore, it can be concluded that the better the implementation of the modern tax system, the higher the level of taxpayer compliance in fulfilling tax obligations. The findings also demonstrate that the modernization of tax administration facilitates tax services, thereby encouraging greater taxpayer awareness and compliance.